Recent advances in methyltransferase biocatalysis. (April 2017) - Bennett, Matthew R; Shepherd, Sarah A; Cronin, Victoria A; Micklefield, Jason
Highlights: S -adenosyl methionine-dependent methyltransferases are ubiquitous in nature. Analogs of S -adenosyl methionine can be produced enzymatically. Crystallography has improved understanding of methyltransferase selectivity. Tandem assays utilizing methyltransferases lead to industrially relevant compounds Abstract : S -adenosyl-L -methionine-dependent methyltransferses are ubiquitous in nature, methylating a vast range of small molecule metabolites, as well as biopolymers. This review covers the recent advances in the development of methyltransferase enzymes for synthetic applications, focusing on the methyltransferase catalyzed transformations with S -adenosyl methionine analogs, as well as non-native substrates. We discuss how metabolic engineering approaches have been used to enhance S -adenosyl methionine production in vivo . Enzymatic approaches that enable the more efficient generation of S -adenosyl methionine analogs, including more stable analogs, will also be described; this has expanded the biocatalytic repertoire of methyltransferases from methylation to a broader range of alkylation reactions. The review also examines how the selectivity of the methyltransferase enzymes can be improved through structure guided mutagenesis approaches. Finally, we will discuss how methyltransferases can be deployed in multi-enzyme cascade reactions and suggest future challenges and avenues for further investigation.